Representações políticas em Dois Irmãos - Braga, Moady de Oliveira (2018)
This dissertation has as object of study the novel of memories Dois Irmãos. It is composed of three chapters, whose main objective is to demonstrate that the conflicts of the twin brothers Yaqub and Omar are a political representation of the wars that took place between the United States of America and the Soviet Union in the context of the Cold War, of the 20th Century. The methodology adopted for the development of said text is the analytical comparative, supported in similar literary works, as well as in compendia of historical records, documentaries and others. The first chapter is a composition that proposes to emphasize points of similarities between the ax novel of Assis Esau and Jacob and Dois Irmãos, of Hatoum, main object of this dissertative work. It shows that the Amazonian author drank the water of the inspiration of his work in Machado sources, just remember as an example, the dispute for the love of the same woman; the possessive and protective profile of the mothers; the constant differences of opinion and behavior of the twins. The second is concerned with comparisons and analogies in demonstrating that the rivalries, disputes, and irreconcilable war between the twin brothers Yaqub and Omar, the central characters of the above-mentioned novel, go far beyond personal or family, fashionable Cain and Abel, Esau and Jacob, both biblical. But rather, a metaphorical demonstration, as representations of a political war of antagonistic ideologies, similar to the two giant characters of the referred Cold War. Since each of the bully brothers also always wanted to defend and impose their ideologies of life. The latter has as its proposal, using the same methodology as the previous ones, to mention some of the traditional characters, which is why they are very present in the Brazilian and universal romanes que literary scenario. Just as you dig deeper into others. They are: the trickster, the negro, the slave, the Indian and the household. Since Domingas, another important character of the novel in study, has indigenous descendants, and when it came to Manaus it became an aggregate of the family of the Lebanese and it impregnated of one of their children, having a boy. Such relations are characterized by analogies and comparisons, as well as being important political representations present in the tragic history of the two rival brothers and their entire family. Keyword: Literature. Double. Politics.